Fuel Subsidy Reform in Sudan : An Assessment of the Direct Welfare Impact on Households - Etang Ndip, Alvin (World Bank, Washington, DC, 2021)
This paper investigates the distributional direct welfare impact on households resulting from fuel subsidy removal. Note that this analysis focuses only on the direct distributional impact. A fuller understanding of the impact of fuel subsidies removal involves analyzing the indirect impact as well. Unfortunately, analysis of the distributional effect of fuel subsidies removal or fuel price increases is heavily constrained by the lack of appropriate data in Sudan. We do not have access to the relevant input-output table that describes the number of monetary transfers between sectors of the economy, making it impossible to simulate the indirect effect of fuel price increases on prices in other sectors. Therefore, the estimated impacts in this paper should be considered as the lower bound of the potential impact, as the overall impact will be higher when indirect impacts are factored. The paper is organized as follows. Section two examines the empirical evidence on the impact of fuel subsidy removal. Section three discusses the methodology and data used in this study. Section four presents an analysis of the welfare impact of fuel subsidies removal. Section 5, the conclusion, provides some suggestions on the way forward. The results from this work would inform policy dialogue with the Government of Sudan regarding the overall economic reforms that are being considered for stabilization of the economy.